2018
DOI: 10.22610/jebs.v9i6.2003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Okun’s Law in Nigeria through the Dynamic Model

Abstract: Unemployment is a persistent challenge for countries, especially the developing ones. Nigeria as a developing country faces a herculean task reducing the increasing spate of joblessness amongst her citizens. Okun’s law explains the relationship between unemployment and economic growth in an economy. This study therefore investigates Okun’s law in Nigeria between 1985 and 2015 through the dynamic model. The generalized method of moments estimation result reveals that that present and past output growth are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Using the Generalised Method of Moments, the examination of the dynamic relationships subsisting between output growth and unemployment in Nigeria between 1970 and 2010 confirmed a non-linear and humpshaped dynamic link (Sanusi, 2012). The connection was being positive at unemployment rates below the threshold of 5.5 per cent and become negative at higher unemployment rates (Adeyeye, 2017). The dynamic research which applied the same generalized method of moment's estimation reports an adverse impact of present and past GDP on the rate of employment in Nigeria between 1985 and 2015.…”
Section: Literature and Empirical Reviewsmentioning
confidence: 98%
“…Using the Generalised Method of Moments, the examination of the dynamic relationships subsisting between output growth and unemployment in Nigeria between 1970 and 2010 confirmed a non-linear and humpshaped dynamic link (Sanusi, 2012). The connection was being positive at unemployment rates below the threshold of 5.5 per cent and become negative at higher unemployment rates (Adeyeye, 2017). The dynamic research which applied the same generalized method of moment's estimation reports an adverse impact of present and past GDP on the rate of employment in Nigeria between 1985 and 2015.…”
Section: Literature and Empirical Reviewsmentioning
confidence: 98%
“…The result suggests that Okun coefficient is not only unstable but varies for different countries, and does not remain constant for Nigeria. Adeyeye et al (2017), investigates Okun's law in Nigeria using dynamic model. The results show that only past output growth has significant effect on unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also other factors that caused violation of Okun law, these are Labor force transfer among sectors, Increasing labor productivity, Increase in the total labor force and inaccuracy of data on unemployment rate and as well as economic growth (Moosa, 2008). Works in Nigeria that found violation of Okun law by finding positive relationship between unemployment and economic growth include Babalola et al (2013), Adeyeye et al (2017), Udude and Nnachi (2017) and Bankole and Fatai (2013).…”
Section: Ardl Bound Testingmentioning
confidence: 99%
“…In other countries, some increases could be seen in various periods. In Nigeria, Adeyeye et al (2017) who used the Toda-Yamamoto Granger non-causality and Generalized Method of Moments found there was no causality between unemployment and economic growth. It can be understood that Okun's argument of bidirectional causality between unemployment and economic growth is invalid for Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it can be indicated that there is an uncertain relationship between the rate of unemployment and output in various countries. For example, the economic growth had a negative and significant effect on the unemployment rate (Abdul-Khaliq et al, 2014;Alamro & Al-dala'ien, 2016;Bande & Martın-RoMan, 2017;Blázquez-Fernández et al, 2018;Darman, 2013;Dritsaki & Dritsakis, 2014;Jibir et al, 2015;Kargi, 2016;Kori Yahia, 2018;Noor et al, 2007;Pierdzioch et al, 2011;Ruxandra, 2015;Soylu et al, 2018;Tatoglu, 2011;Zanin & Marra, 2012), the Okun's coefficient was not significant (Apergis & Rezitis, 2003;Arewa & Nwakanma, 2012;Astuti, 2016;Yaumidin, 2009), there were positive coefficients in the regression and it implied that the Okun's legal interpretation did not apply (Bankole & Fatai, 2013), there was no causality between economic growth and unemployment rate (Adeyeye et al, 2017), there was a two-way causality between unemployment and output growth (Boďa & Považanová, 2015;Noor et al, 2007), and the Okun's coefficient was different for each country (Azorín & de la Vega, 2017;Bande & Martın-RoMan, 2017;Dixon et al, 2016;Hutengs & Stadtmann, 2013;Moosa, 1997;Rahman & Mustafa, 2017;Silvapulle et al, 2004). Based on these findings, the following hypotheses was suggested:…”
mentioning
confidence: 99%